PENGARUH PERSONAL SELLING DAN PROMOSI PENJUALAN TERHADAP PENINGKATAN VOLUME PENJUALAN PRODUK MLM SM DI KARANGANYAR - PUJIANI, DEWI (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2014)
This research there were some formulation of the problem among others: (1) is there any influence partially or simultaneous personal selling and the sales volume of SM MLM product in Karanganyar? (2) between personal selling and sales promotion where does that have an effect on increased sales volumes SM MLM product in Karanganyar? The company will finance the cost of promotions in accordance with the budget determined by the company. Measurements of the variables in this study using a Likert Scale by spreading the product to the customer questionnaire SM MLM product. The contribution of this research is to know the influence of personal selling and sales promotion to increase sales volume. The hypothesis of this research is: 1) there is influence significant between personal selling and sales promotion to increase sales of SM MLM product in Karanganyar; 2) the most dominant variable the increase in sales volume SM MLM product in Karanganyar is variable product sales promotion. Multiple linear regression test results obtained regression coefficient values larger than personal selling, so the sales promotions more dominant against an increase in the volume of sales compared to other variables. Keywords: Promotional mix, personal selling, sales promotion, sales volume